M6A modification: A mechanism for protecting hematopoietic development in mammals. (9th October 2020) - Gao, Jiayin; Yan, Jialong; Huang, Zhen; Chen, Linxi
Abstract: N 6 ‐methyladenosine (m 6 A) is one of the most common internal modifications in messenger RNA, which is necessary for cell physiological activities. A recent study shows that during mammalian hematopoietic development, loss of m 6 A modification leads to the aberrant production of double‐stranded RNA, which results in the abnormal activation of innate immune response, and ultimately leads to hematopoietic failure. Accordingly, m 6 A modification provide us an attractive direction for us to understand mammalian hematopoietic development and innate immune response.